Zawsze w pobliżu. Ochrona prezydentów Rzeczypospolitej - Szumiec-Zielińska , Elżbieta (Studia Europaea Gnesnensia, 2022)
The paper discusses issues relating to the protection of the presidents in the Second Republic of Poland. Selected regulations are outlined to show the legal foundation on which a system for ensuring the safety of people protected by dedicated services was organized. Subsequently, the author shows how the presidential security operated so that the heads of state could feel safe at work, in their residences, during travels and leisure.